Reseña a Álvarez González, Albert & Navarro, Ía (eds.), 2017. Verb Valency Changes. Theoretical and typological perspectives. Ámsterdam/Filadelfia: John Benjamins. - Tubino Blanco, Mercedes (Cuadernos de Lingüística de El Colegio de México, 2018)
-